ARGUMENTASI MATEMATIS SISWA SMA DALAM MENYELESAIKAN MASALAH GEOMETRI RUANG DIMENSI TIGA : Studi Fenomenologi Hermeneutik - Ega Charisma, - (2022)
This study aim to describe student's mathematical argumentation solving three dimensional shape problem. This study used qualitative research with hermeneutical phenomenology approach involving on twelve 12th grade student in senior high school. Student's mathematical argumentation was identified through mathematical argumentation test and interview with selected participant. The mathematical argumentation focus on distance in three dimensional shape ( the distance between two point, a point to a line, and a point to plane). Based on the results and discussion of the research, it was showed that most of the students lack on construct their mathematical argumentation. It was showed on their answer where student's answer do not contain at least three main component (data, warrant and claim). Most of students have trouble in construct their mathematical argumentation related to the concept of distance between a point to a line. Lack of understanding on geometry concept causes students failed to construct their mathematical argumentation. Furthermore, non routine problem also be an obstacle for student to construct a mathematical argumentation. Keywords: distance in three dimensional shape, high school student, mathematical argumentation, mathematical understanding, reasoning and proof.